Theoretical analysis of a double stages erbiumdoped fiber amplifier - Al-Khateeb, Khalid A. Saeed; Mohammed, M. A.; Naji, Ahmed Wathik; Ibrahim, H. F. H. (2010)
Many configurations of EDFA producing triple pass EDFAs have been used, however, only two configurations are commonly used in the optical fiber communication system due to their high performance. Those two configurations are configured in a double stage EDFA. The first configuration is (configuration A) consists of a single-pass EDFA as the first stage and a double-pass EDFA as the second stage. The second configuration is (Configuration B) which consists of a double-pass EDFA as the first stage and a single-pass EDFA as the second stage. The Literature shows the use of triple pass EDFA is either with configuration A or configuration B and literature also shows there is no theoretical analysis and comparison between the performance of two Triple-pass EDFA configurations A and B. This paper focus on the performance analysis of both configurations A and B. The importance of this research is the theoretical analyses that analyze the performance of those two configurations and illustrate a comparison between them. This comparison is important to show which of the two configurations is more reliable in amplifying optical signal for the fiber optic communication systems.